UNDERSTANDING OF TEACHERS AND ELEMENTARY STUDENTS ON CLIMATE CHANGE MITIGATION AND ISSUES - Lungguh Puri Pramswari; Atep Sujana; Ari Widodo (Sekolah Pascasarjana UPI, 2022)
Climate change is a global challenge that threatens the world today. To deal with the problem of climate change, it is necessary to understand the issue of climate change. The purpose of this study was to determine the understanding of elementary school teachers and students about the issue of climate change. Data were obtained through open and closed questionnaires. Data were analyzed qualitatively. The subjects of this study were 45 elementary school teachers and 25 elementary students. The results of the study show that 1) all respondents of teachers and elementary school students consider it important to find solutions and understandings to overcome climate change; 2) students assume that climate change is a simple problem, this is shown from the student response data, namely 52% know that an increase in greenhouse gases can cause climate change. In addition, students' difficulties in reducing the impact of climate change such as using motorized vehicles when going to school. The understanding of teachers and elementary school students on the issue of climate change is still lacking, so there needs to be awareness within each of them to encourage them to take climate change mitigation actions.